Le Ralliement : journal hebdomadaire illustré (Bruxelles, 1908)
"Periodiciteit: wekelijksHoofdredactie: Paul Janson, E. Feron, E. Robert, P. Hanrez, G. Lorand, A. Lambiotte, Hermann Dumont (Comité de direction)Redactie: Ch. Magnette, Hermann Pargameni, Maurice Saey, Lucien Vertongen, F. Ley, F. Rosseels, Franz FoulonBeheer/Administratie: rue des Coteaux 198, Bruxelles (12 apr 1908) / rue Verboekhaven 61, Bruxelles (6 sep 1908)Drukker/Drukkerij: Imp. Du Progrès, V. Feron, rue Verboeckhaven 61, Bruxelles"